2021
DOI: 10.1111/birt.12559
|View full text |Cite
|
Sign up to set email alerts
|

Giving birth during the COVID‐19 pandemic, perspectives from a sample of the United States birthing persons during the first wave: March‐June 2020

Abstract: Background:The COVID-19 pandemic forced hospitals in the United States to adjust policy and procedure in order to provide safe care and prevent the spread of disease. At the beginning of the pandemic, media and case reports described pressure for medical interventions, visitor restrictions, separation from newborns, and an increase in patient demand for community birth (home and birth center). The purpose of this study was to describe birth experiences during the COVID-19 pandemic centering the birthing person… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
67
1
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(79 citation statements)
references
References 15 publications
4
67
1
5
Order By: Relevance
“…Women of color had lower birth satisfaction in our study, similarly to Breman et al (2021) and Janevic et al (2021) who found that Black and Latina women had reduced birth satisfaction during the COVID-19 pandemic. These findings are consistent with Hamm et al (2019) that previously reported racial disparities in birth satisfaction.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Women of color had lower birth satisfaction in our study, similarly to Breman et al (2021) and Janevic et al (2021) who found that Black and Latina women had reduced birth satisfaction during the COVID-19 pandemic. These findings are consistent with Hamm et al (2019) that previously reported racial disparities in birth satisfaction.…”
Section: Discussionsupporting
confidence: 86%
“…The COVID-19 pandemic has affected women's birth experiences ( Breman et al, 2021 ; Burgess et al, 2021 ). Women giving birth during the pandemic have shown a high likelihood of experiencing a traumatic birth, perinatal mental health disruption, and poor maternal–infant bonding ( Hessami et al, 2020 ; Mayopoulos et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The COVID-19 pandemic is a public health crisis that has dramatically affected the pregnancy experience ( Breman et al, 2021 ; Burgess et al, 2021 ). To accommodate social distancing mandates, prenatal care guidelines were developed ( American College of Obstetricians and Gynecologists, 2020 ; Centers for Disease Control and Prevention, 2020 ).…”
mentioning
confidence: 99%
“…2,3 Additionally, survey data suggest that there has been an increase in out-of-hospital births during the pandemic. [4][5][6] We assume that infants born outside the hospital setting are more likely to experience delays in or fail to complete newborn hearing screening. 7 The next step in EHDI is to confirm hearing loss by 3 months of age, typically with auditory brainstem response (ABR) testing.…”
mentioning
confidence: 99%